Evaluation of Acacia- Guar Gum Combination as Delayed Release Coating Former on Solid Placebo Tablets - Suad Y. Alkarib; Deina E. MohamedElhassan (Journal of Advanced Pharmaceutical Science And Technology, 2021)
Objectives The present study addresses evaluation of acacia-guar gum combination as an enteric former for tablet coating aiming to add knowledge on how develop the ability of enteric forming ability of acacia-guar combination. Methods Five formulations of enteric coating solution incorporating guar gum as delayed release polymers along with film coating material acacia gum followed by CMC and glycerin as plasticizer and coloring agents were prepared to coat placebo tablet cores. Different enteric coating formulations organized in different acacia : guar gum ratios as 1:1, 1:2, 1:3, 1:4 and 1:6 were sprayed on placebo tablets surface resulted different delayed coated tablets (F1,F2,F3,F4 &F5) respectively. General appearance and physical parameters were evaluated of each. Enteric coated tablets that revealed promising properties were subjected to accelerated stability study for 3 months to explore the influences of physical aging on tablet coat properties. Results Physical parameters of enteric coated tablets post coating within the range of pharmacopeia specification. The disintegration test was carried out in pH 1.2 and pH 6.8 at 37ºC. F1, F2 and F3 enteric tablets disintegrated immediately with no acid resistance compared F4 and F5 enteric tablets showed good acid resistance coat with smooth tablet surfaces and no coat defects. F5 formula contain acacia: guar gum as 1:6 ratio showed delayed release for 30min in pH 1.2 and 15min in phosphate buffer. The study statistically analyzed and concluded that, an efficient and stable acacia-guar enteric coat is achievable with no effect on tablets physical parameters. Guar gum at 60% as a delayed tablet coating material capable of protecting the tablets core from being released in acidic media and be release in the alkaline buffer as well as stable coat under accelerated storage for three months.
Keywords: Enteric Coating